When all is said - Griffin, Anne, 1969- (New York : Thomas Dunne Books, St. Martin's Press, 2019)
"If you had to pick five people to sum up your life, who would they be? At the bar of a grand hotel in a small Irish town sits 84-year-old Maurice Hannigan. Over the course of this evening, he will raise five toasts to the five people who have meant the most to him. Through these stories - of unspoken joy and regret, a secret tragedy kept hidden, a fierce love that never found its voice - the life of one man will be powerful and poignantly laid bare.
"A novel" -- Cover.
Keywords: Older men -- Ireland -- Fiction; Bars (Drinking establishments) -- Ireland -- Fiction; Reminiscing in old age -- Fiction; Ireland -- Fiction; Domestic fiction